2018
DOI: 10.1101/gr.231357.117
|View full text |Cite
|
Sign up to set email alerts
|

Human-specific features of spatial gene expression and regulation in eight brain regions

Abstract: Molecular maps of the human brain alone do not inform us of the features unique to humans. Yet, the identification of these features is important for understanding both the evolution and nature of human cognition. Here, we approached this question by analyzing gene expression and H3K27ac chromatin modification data collected in eight brain regions of humans, chimpanzees, gorillas, a gibbon, and macaques. An analysis of spatial transcriptome trajectories across eight brain regions in four primate species reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 71 publications
6
69
0
Order By: Relevance
“…1H). Overall, in agreement with previous works [Sousa et al, 2017a;Xu et al, 2018], more differences mapped to the human lineage (the average n=712) than to the chimpanzee (n=641) or bonobo (n=640) lineages.…”
Section: Regional Analysis Of the Human-specific Gene Expression Diffsupporting
confidence: 92%
See 1 more Smart Citation
“…1H). Overall, in agreement with previous works [Sousa et al, 2017a;Xu et al, 2018], more differences mapped to the human lineage (the average n=712) than to the chimpanzee (n=641) or bonobo (n=640) lineages.…”
Section: Regional Analysis Of the Human-specific Gene Expression Diffsupporting
confidence: 92%
“…While the expression differences shared among brain regions often represent molecular and functional changes not specific to the brain [Khaitovich et al, 2004a;Khaitovich et al, 2005], differences particular to individual brain regions tend to be associated with specific brain functions [Khaitovich et al, 2004a]. Recent studies examining eight and 16 brain regions in humans and closely related NHPs expanded these results further by revealing the rapid expression evolution of several subcortical regions in addition to the neocortical areas [Sousa et al, 2017;Xu et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Even if few percentages of genes have different trajectories in non-human primate and human in contrast to rodent, this model can help to understand brain development, but it cannot model all features found in human [79,81]. In fact, comparison between non-human primate and human brains transcriptome analysis showed human specificity in gene expression profiling [82][83][84] with demonstration that genes differentially expressed are principally upregulated in human brains in contrast to other organs [85,86]. In addition, the transcriptome remodeling during postnatal periods appears delayed in human brain comparing to non-human primate [87].…”
Section: Perspectives For the Coming Years: From The Use Of New In-vimentioning
confidence: 99%
“…With enormous amounts of transcriptome (RNA-seq) data from multiple tissues with diverse species available, it is the exciting time for evolutionary biologists to address how gene regulation plays a key role in phenotypic innovations (King and Wilson 1975;Lehner 2013) (e.g., Wang, et al 2009;Brawand, et al 2011;McCarthy, et al 2012;Necsulea and Kaessmann 2014;Xu, et al 2018;Cardoso-Moreira, et al 2019). To help achieve this goal, development of statistically-sound methods that enable researchers to study the pattern of transcriptome evolution is desirable (Gu and Su 2007;Pereira, et al 2009;Gu, et al 2013;Gu 2016;Ruan, et al 2016;Gu, et al 2017;Sudmant, et al 2015;Yang et al 2018;Gu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Each statistical hypothesis testing (usually for each gene) results in a p-value summarizing the level of statistical significance of the observed differential gene expression. Xu et al (2018) conducted an analysis to predict differentially expressed (DE) genes between the human and chimpanzee in several brain regions. Their study indicated that detection of DE genes between species is a valuable approach to understanding the pattern of transcriptome evolution.…”
Section: Introductionmentioning
confidence: 99%